Relationship Between Exclusive Breastfeeding and Basic Immunization Status Related with Stunting in Toddlers Aged 12-24 Months - Ni Komang Ayu Resiyanthi; Ni Luh Gede Puspita Yanti (GLOBAL HEALTH SCIENCE GROUP, 2021)
The nutritional problems faced by Indonesian children in the long term will cause problems in the growth and development of children. The incidence of growth and development problems due to malnutrition is commonly called stunting. The World Health Organization (WHO) in 2018 stated that the incidence of stunting under five in the world reached 22.9% or 154.8 million children under five. The purpose of this study was to determine the relationship between exclusive breastfeeding and basic immunization status with the incidence of stunting in children aged 12-24 months. The method used in this study is a quantitative method with a descriptive correlational research approach, namely an approach by testing the relationship between variables. The type of research used in this study is a cross sectional study. This study uses Consecutive Sampling, namely the selection of samples by determining subjects who meet the research criteria to be included in the study until a certain time limit so that the number of respondents is met. the results of the analysis of the relationship between breastfeeding and the incidence of stunting obtained the highest data was exclusive breastfeeding with no stunting as many as 92 respondents (87.0%). The results of the Rank-Spearman statistical test obtained p-value = 0.000 < (0.05). The results of the analysis of the relationship between the immunization status of children and the incidence of stunting obtained the highest data was the complete immunization status of children without stunting as many as 92 respondents (70.7%).